2017
DOI: 10.1111/are.13369
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating spawning performance among captive Florida pompano Trachinotus carolinus broodstock using microsatellite-based parentage assignment

Abstract: Florida pompano has been identified as a promising candidate for commercial‐scale aquaculture production, but to date, little information is available regarding captive broodstock spawning characteristics. Genetic markers were tested for their power in monitoring mating outcomes and potential in analysing heritability of rapid growth trait in Trachinotus carolinus. A total of 20 unrelated adults (10 females and 10 males) were chosen for a hormone‐induced mass spawning event. The 515 fastest growing and 485 slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In another recent study conducted at MOTE, Ma et al (2017) evaluated the spawning performance of captive pompano broodstock using microsatellite-based DNA profiling in an effort to determine parentage assignment of offspring. The authors recommended employment of a genetically rigorous breeding plan, with optimal numbers of dams and sires (e.g., one or two females to three males), in order to ensure genetic diversity of offspring.…”
Section: Reproduction and Larviculturementioning
confidence: 99%
See 1 more Smart Citation
“…In another recent study conducted at MOTE, Ma et al (2017) evaluated the spawning performance of captive pompano broodstock using microsatellite-based DNA profiling in an effort to determine parentage assignment of offspring. The authors recommended employment of a genetically rigorous breeding plan, with optimal numbers of dams and sires (e.g., one or two females to three males), in order to ensure genetic diversity of offspring.…”
Section: Reproduction and Larviculturementioning
confidence: 99%
“…Pompano also exhibit a wide size variation among cohorts, with slower growing fish depressing overall FE, suggesting a genetic component that could be potentially be addressed through a selective breeding program. Recent evidence suggests this is a much needed and viable approach (Ma et al, 2017).…”
Section: Nutrition and Feed Developmentmentioning
confidence: 99%
“…In total we had 790 European sea bass sampled at~11 months available for genotyping and sex ratio analysis. Genotyping unambiguously assigned 764 fish to the parents but showed that most (99%) offspring came from dam b, meaning that the rate of fertilization of the eggs of dam a was low, that the viability of the offspring of dam a was low, or both, something that is frequent in fish [45][46][47][48][49][50][51]. Thus, the few offspring of dam a were no longer considered and we only report results related to the four families derived from dam b.…”
Section: Genotyping and Sex Ratiosmentioning
confidence: 99%
“…Good quality seeds are only produced from good quality broodstock and using good fish hatchery methods. The provision of superior silver pompano parents in supporting the sustainability of seed production activities is needed, one of which is by selecting superior traits from prospective fish parents (Ma, et al, 2017). The genetic quality of a group determines the phenotypic appearance of the group.…”
Section: Introductionmentioning
confidence: 99%